Legal Protection For Juvenile, Female, and Elderly Prisoners in The Provisions of Facilities - Warjiyati, Sri (Nursyam Centre, 2023)
A Penitentiary is an implementing institution of the criminal system that functions to foster prisoners, including in this case women who undergo criminal punishment are required to participate in a whole series of formation activities in prisons. In this case, the effectiveness of the formation of prisoners can set a good example and example to others, especially for women, children, and elderly prisoners. Then the supporting factors can be used as examples for better in the future and factors that can hinder the coaching can be found better solutions. The purpose of this study is to determine the pattern of coaching female, child, and elderly prisoners and determine the inhibiting and supporting factors of coaching. To overcome problems in the implementation of the development of women, children, and elderly prisoners, synergy is needed between all parties involved, ranging from prisoners, correctional officers, and related agencies to cooperate in the implementation of training for women, children, and elderly prisoners. For this reason, it is necessary to handle and coach to achieve better goals, and if the prisoner has come out, it will create an independent character and have a better leadership spirit